THE JURISDICTION OF THE HIGH COURT UNDER ARTICLE 199 OF THE CONSTITUTION OF PAKISTAN: A CASE STUDY OF THE OIL AND GAS REGULATORY FRAMEWORK - Ahmad, Rizwan (The journal of contemporary issues in business and government, 2025)
This research paper critically examines the role of judicial review in preventing executive overreach in Pakistan, with a particular focus on the constitutional jurisdiction exercised by courts under Article 199. It highlights the judiciary's role in reinforcing regulatory compliance, ensuring procedural fairness, and protecting economic rights against arbitrary administrative actions. By analyzing key judicial precedents, including recent rulings by the Courts, this paper illustrates how courts have maintained the supremacy of law in regulatory matters, particularly within the petroleum sector governed by the Oil and Gas Regulatory Authority Ordinance, 2002. Additionally, the paper explores how judicial intervention serves as a safeguard against the misuse of administrative authority, compelling regulatory bodies such as OGRA to function within their legally defined scope. A comparative analysis of judicial review frameworks in the UK and USA provides further insight into how courts in different jurisdictions balance executive discretion with constitutional oversight. The research concludes that judicial vigilance remains crucial for upholding constitutionalism, regulatory transparency, and economic freedoms in Pakistan, reinforcing the principle that no administrative authority is above the law. This research paper critically examines the role of constitutional jurisdiction in preventing executive overreach in Pakistan, focusing on the regulatory framework governing petroleum businesses. It explores the significance of judicial review in administrative actions, emphasizing the limitations imposed by the Oil and Gas Regulatory Authority Ordinance, 2002, and the Pakistan Oil (Refining, Blending, Transportation, Storage, and Marketing) Rules, 2016. The paper delves into the broader implications of constitutional jurisdiction on regulatory governance, the protection of economic rights, and the role of the judiciary in ensuring fair and lawful administrative practices. By analyzing judicial precedents, statutory frameworks, and governance principles, this paper highlights the importance of lawful authority in executive decision-making and its impact on the business environment in Pakistan.